THE IMPACT OF COVID-19 PANDEMIC ON METAL MINERAL COMMODITIES IN INDONESIA AND THEIR MITIGATION IN MINING ACTIVITIES: Desk studi - wahyu wahyu garinas (Jurnal Sains dan Teknologi Mitigasi Bencana, 2020)
The Covid-19 pandemic in 2020, has affected all mining sectors. The price of mining materials index is very low due to the Covid-19 pandemic and also when compared to other pandemics such as SARS, HN1, and Ebola. The price of the metal index such as iron, aluminum, nickel, zinc, copper) almost all fell and only high gold metals are increasingly expensive. The large mining companies continue their production and they use health protocols. For the continuity of mining operations, the company creates stages and strategies in mining operations (teamwork schedule, employee location, working time, number of workers, evacuation of employees). For the continuity of the company's operations, the company plans: responding to an emergency situations (pandemic), build the company's resilience, recover the company from impact, develop an action plan and build the foundation of the company to rise in the new normal time. The company conducts mitigation and protection individually and in groups and creates health campaigns digitally. In mining operations, the company develops its operational activities by implementing health protocols such as avoiding many people and making mine operational plans that follow health protocols.  Keywords: Covid-19 pandemic, mineral commodity, index value, health mitigation.